Studies on the Interaction Mechanism Between Cu(II) Ternary Complex and DNA - GUO, FENG (Asian Journal of Chemistry, 2010)
A new complex of Cu(II) with N-(2-hydroxy-1-naphthalidene) glycine Schiff base and 1,10-phenanthroline was synthesized and characterized by elemental analysis, molar conductivity, IR and thermal decomposition. The fundamental electrochemical characteristics of a Cu(II) ternary complex have been studied and the interactivity of copper complex with DNA was also studied by cyclic voltammetry and fluorescence spectrum. The results suggest that the binding ratio between the Cu ternary complex and DNA was calculated to be 1:1 and the binding constant was 6.05 × 104 L mol-1.